2014
DOI: 10.1021/jf5004539
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Fluorescent Probe for Rapid Detection of Bisulfite through 1,4-Addition Reaction in Aqueous Solution

Abstract: A ratiometric fluorescent probe based on a positively charged benzo[e]indolium moiety for bisulfite is reported. The bisulfite underwent a 1,4-addition reaction with the C-4 atom in the ethylene group. This reaction resulted in a large emission wavelength shift (Δλ = 106 nm) and an observable fluorescent color change from orange to cyan. The reaction could be completed in 90 s in a PBS buffer solution and displayed high selectivity and sensitivity for bisulfite. A simple paper test strip system was developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 31 publications
1
51
0
2
Order By: Relevance
“…Brain tissue as well as spleen, lung, heart, kidney, liver, serum, muscle, colon and testicle were separated from rats and homogenized immediately as 16 described by Zhao, Xu and co-workers in previous work [37,44]. A calibration curve was constructed with sulfite concentrations ranging from 1.0 M to 20.0 M (R = 0.9988) (Fig.…”
Section: In Vivo Sulfite Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain tissue as well as spleen, lung, heart, kidney, liver, serum, muscle, colon and testicle were separated from rats and homogenized immediately as 16 described by Zhao, Xu and co-workers in previous work [37,44]. A calibration curve was constructed with sulfite concentrations ranging from 1.0 M to 20.0 M (R = 0.9988) (Fig.…”
Section: In Vivo Sulfite Imagingmentioning
confidence: 99%
“…Hence, fluorescent probes for sulfite and/or bisulfite have been reported [15][16][17][18] and used for imaging of intracellular sulfite/bisulfite levels [19][20][21]. However, to the best of our knowledge, no probes for the determination of sulfite distribution in subcellular organelles are available.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional analytical techniques including spectrophotometry [19], spectrofluorimetry [20], chemiluminescence [21], chromatography [22] and enzymatic techniques [23], optical sensors have drawn significant attentions because of their simplicity, sensitivity and virtues in real-time observation and visualization. More and more organic dye-based optical sensors have been designed such as coumarin derivatives [24e26], benzo[e]indolium derivatives [27,28], rhodamine derivatives [29], naphthalimide derivatives [30,31] and dipyrromethene derivatives [32]. However, few bisulphite optical sensors are based on heavy-metal complexes, which have more advantages over organic dyes with low-lying excited states or long-wavelength emission [33e35].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, the fluorescence method has received much attention due its the advantages of convenience, high sensitivity, fast response and ease of live-cell imaging (14)(15)(16). Fluorescent probes for SO 3 2-have been mainly based on the addition to an aldehyde moiety or a nucleophilic addition (17)(18)(19)(20)(21)(22)(23)(24)(25), and levulinate cleavage mediated by SO 3 2- (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). However, these probes suffer from low selectivity in the presence of biothiols such as cysteine, homocysteine, glutathione and a relatively long reaction time, which are not suitable for detecting or imaging SO 3 2-in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, these probes suffer from low selectivity in the presence of biothiols such as cysteine, homocysteine, glutathione and a relatively long reaction time, which are not suitable for detecting or imaging SO 3 2-in living cells. Recently, Wu et al (33) and Sun et al (34) have reported some probes with improved selectivity, however, most of them have slow response times, which limits their utility. As a result, the development of a fluorescent probe for the quantitative detection of SO 3 2-with highly sensitivity, fast response and selectivity has remained a challenge.…”
Section: Introductionmentioning
confidence: 99%